L'insécurité linguistique chez les étudiants du département de traduction Cas des étudiants de première année traduction à L’université de Laghouat - BENSLIM ,samira; BELGHOUAR ,Sara (Faculty of Letters and Foreign Languages Department of English, 2025)
This thesis assesses oral language insecurity among first-year students in translation department of Laghouat University. Using a mixed-method approach with quantitative questionnaires and qualitative interviews, this thesis investigates students’ views of their oral proficiency in Arabic, French and English. The results show that most students clearly feel considerable discomfort when giving oral presentations -- especially in French because of their regret for past errors, fear of judgment, and limited practicing time. This insecurity inhibits students participating in class, their learning process becomes somewhat limited. Finally, the thesis provides recommendations to increase students’ oral expression in the classroom -- i.e., providing opportunities for regular oral activities and sharing reciprocal feelings and experiences with other students in order to improve classroom moral